2020
DOI: 10.3390/ijerph17217731
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Behaviour Change Techniques within Interventions to Reduce Environmental Tobacco Smoke Exposure for Children

Abstract: Children are particularly vulnerable to environmental tobacco smoke (ETS). There is no routine support to reduce ETS in the home. We systematically reviewed trials to reduce ETS in children in order to identify intervention characteristics and behaviour change techniques (BCTs) to inform future interventions. We searched Medline, EMBASE, CINAHL, PsycINFO, ERIC, Cochrane Central Register of Controlled Trials, and Cochrane Tobacco Addiction Group Specialised Register from January 2017 to June 2020 to update an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
(344 reference statements)
1
10
0
Order By: Relevance
“…Secondhand exposure to e-cigarette and tobacco products may normalise tobacco use behaviours among youth, lowering perceptions of danger and increasing susceptibility to the use of e-cigarettes and other tobacco products 50 51. Individual or family-centred interventions are needed at home to raise awareness of the adverse cumulative consequences of exposure to tobacco product use in the home 52 53…”
Section: Discussionmentioning
confidence: 99%
“…Secondhand exposure to e-cigarette and tobacco products may normalise tobacco use behaviours among youth, lowering perceptions of danger and increasing susceptibility to the use of e-cigarettes and other tobacco products 50 51. Individual or family-centred interventions are needed at home to raise awareness of the adverse cumulative consequences of exposure to tobacco product use in the home 52 53…”
Section: Discussionmentioning
confidence: 99%
“…In terms of effectiveness, no gold standard approach exists for identifying BCTs (Michie et al, 2018). We therefore identified the 'promising' BCTs following a method adopted in previous studies (e.g., Ahmed et al, 2021;Brown et al, 2019Brown et al, , 2020Lorencatto et al, 2012). Specifically, a BCT was defined as promising if it was present in at least 25% of all interventions and was present in at least two effective interventions.…”
Section: Data Extractionmentioning
confidence: 99%
“…However, there is no agreed method for identifying effective BCTs and each approach used to date has limitations (Michie et al, 2018). Following previous work (e.g., Ahmed et al, 2021;Brown et al, 2019Brown et al, , 2020Lorencatto et al, 2012), the approach used has the potential to identify BCTs that could be effective. Third, some studies only had short-term follow-up meaning it is unclear whether initial behavior change was sustained over time.…”
Section: Limitationsmentioning
confidence: 99%
“…Interventions trialed in this setting in the USA have included motivational interviewing and the offer of incentives, demonstrating some promise [ 28 ]. A recent review of interventions to prevent ETS in paediatric settings concluded that interventions should incorporate effective behaviour change techniques (BCTs) [ 29 ], suggesting the need to develop a tailored intervention to support families in NICUs specifically. Behaviour change interventions are complex by nature, comprising multiple components including different mechanisms of delivery in addition to BCTs [ 30 ].…”
Section: Introductionmentioning
confidence: 99%